1997
DOI: 10.1007/s002620050345
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumor effects of murine interferon- γ -inducing factor/interleukin-18 in mice bearing syngeneic Meth A sarcoma malignant ascites

Abstract: Interferon-gamma-inducing factor/interleukin-18 is a novel cytokine that reportedly augments natural killer (NK) activity in human and mouse peripheral blood mononuclear cell cultures in vitro and has recently been designated IL-18. In this study, IL-18 exhibited significant antitumor effects in BALB/c mice challenged intraperitoneally (i.p.) with syngeneic Meth A sarcoma when administered i.p. on days 1, 2 and 3 after challenge. Intravenous (i.v.) administration also induced antitumor effects in the tumor-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(89 citation statements)
references
References 25 publications
1
88
0
Order By: Relevance
“…10 IL-18 also has in vivo antitumor effects against Meth A sarcoma. 11 These biological activities are similar to those of IL-12. In fact, IL-12 and IL-18 exhibit a remarkably synergistic effect on IFN-␥ induction by stimulated T cells.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…10 IL-18 also has in vivo antitumor effects against Meth A sarcoma. 11 These biological activities are similar to those of IL-12. In fact, IL-12 and IL-18 exhibit a remarkably synergistic effect on IFN-␥ induction by stimulated T cells.…”
supporting
confidence: 53%
“…They concluded that the cells responsible for the cytotoxic activity induced by IL-18 were CD4 ϩ T cells. 11 Dao et al also showed that IL-18 selectively enhances the Fas ligand-mediated cytotoxicity of T helper 1 cells. 33 Considering these reports and our data, CD4 ϩ T cells appear to be essential for the antitumor effects of IL-18.…”
Section: Discussionmentioning
confidence: 98%
“…However, previous studies have shown that depletion of NK cells from immunocompetent mice using anti-asialo GM1 Ab abrogated the IL-18-mediated antitumor effect. 31 (Table 2), secretion of IL-18 might be inefficient to fully activate the immunocompetent cells. We also found that the loss of tumorigenicity of Colon 26/IL-18 cells when they were inoculated s.c. in immunocompetent mice was abolished when mice were pretreated with anti-IL-12 Ab (data not shown).…”
Section: Antitumor Effect In Immunocompromised Hostsmentioning
confidence: 99%
“…IL-18 induces IFN-γ production, promotes Th1 cell development and NK activation [54], making this cytokine potentially beneficial as an immunotherapeutic agent against cancer. Indeed, IL-18 has been effective in various experimental tumor models [55][56][57]. However, IL-18 is also implicated in tumor progression.…”
Section: Il-18/il-12mentioning
confidence: 99%